Chemical and biological studies on Bridelia ferruginea grown in Nigeria. Issue 2 (17th January 2019) - Afolayan, Michael; Srivedavyasasri, Radhakrishnan; Asekun, Olayinka T.; Familoni, Oluwole B.; Ross, Samir A.
Abstract: Phytochemical investigation of the methanolic extract of dried leaves of Bridelia ferruginea led to the isolation and identification of fourteen compounds (1 –14 ): compound1 [mixture of palmitic, stearic and oleic acids], stearyl monoester of 2- O - β -ᴅ-glucosylglycerol (2 ), 6 β -hydroxy-(20 R )-24-ethylcholest-4-en-3-one (3a ), 6 β -hydroxy-(20 R )-24-ethylcholest-4, 22-dien-3-one (3b ), lutein (4 ), vomifoliol (5 ), corilagin (6 ), kaempferide-3- O - β -ᴅ-glucoside (7 ), myricetin (8 ), isomericitrin (9 ), isoquercetin (10 ), myricitrin (11 ), quercitrin (12 ), rutin (13 ), and β -sitosterol glucoside (14 ). The total extract exhibited moderate activity towards CB2 receptor and 90% inhibition against leishmanial pathogen Trypanosoma brucei . Compound4 exhibited 73% displacement in CB2 receptor with IC50 56.47 μM, and 93% inhibition towards T. brucei with IC50 4.16 μM. Compound11 showed 99% inhibition towards Escherichia coli with IC50 1.123 μM. Abstract :